ICTV Virus Taxonomy Profile: Arenaviridae - Radoshitzky, Sheli R; Buchmeier, Michael J; Charrel, Rémi N; Clegg, J Christopher S; Gonzalez, Jean-Paul J; Günther, Stephan; Hepojoki, Jussi; Kuhn, Jens H; Lukashevich, Igor S; Romanowski, Víctor; Salvato, Maria S; Sironi, Manuela; et al. (Journal of general virology, 2019)
Members of the family Arenaviridae produce enveloped virions containing genomes consisting of two or three single-stranded RNA segments totalling about 10.5 kb. Arenaviruses can infect mammals, including humans and other primates, snakes, and fish. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the family Arenaviridae, which is available at www.ictv.global/report/arenaviridae.